Karakteristik Pasien Epilepsi di RSUD dr. Doris Sylvanus di Palangka Raya - Parhusip, Luther; Tori, Marthin; Br Surbakti, Ranintha; Lestarisa, Trilianty; Toemon, Angeline Novia (Fakultas Kedokteran Universitas Palangka Raya, 2025)
electrical charges in neurons in the brain. Globally, an estimated 5 million people are diagnosed with epilepsy each year. In Indonesia until now there is no definite incidence data because many people with epilepsy are not detected or not visit health centers. This study aims to determine characteristics of epilepsy patients based on age, gender, type of epilepsy, education level, occupation, ethnicity, type of medication, and amount of medication in epilepsy patients at Dr. Doris Sylvanus Hospital. Observational descriptive method with retrospective approach, research data were taken from medical record data for epilepsy patients in 2021-2022. In this study, there were 93 epilepsy patients, dominated by the age group <20 years (45%), male gender (51%), not working (74%), high school (37%), Dayak (51%), type of generalized epilepsy (64%), number of monotherapy drugs (58%), type of valproic acid drug (30%). The characteristics of epilepsy patients at RSUD dr. Doris Sylvanus Central Kalimantan in 2021-2022 in the age group <20 years, male, not working, high school, Dayak tribe, general epilepsy type, number of monotherapy drugs with valproic acid type of drug